Numerical and experimental study on the effect of cab- extender on the flow characteristics of a tractor-trailer - Syed Mohamed Ali, Jaffar; Omar, Ashraf Ali; Nasikin, Mohd Faiz Diuzzaman (Penerbit Akademia Baru, 2019)
The aerodynamic drag on trucks can be reduced by use of active and passive techniques. In this work a passive method of using a cab-extender that is attached to the rear of the tractor is attempted. This cab-extender will help in reducing the drag force that act on the truck by minimizing the gap between the tractor and trailer. In this study, a tractor-trailer model was fabricated and tested in a low speed wind tunnel for its aerodynamics characteristics and the effect of cab-extender was also studied. Later Solid Works CFD package was used to study numerically the effect of this cabextender on the aerodynamics of the truck and the results were validated against the experimental results. Finally using CFD approach the best angle of the cab-extender was reported for minimum drag. © 2019 Penerbit Akademia Baru.